The Flattening Firm: Evidence from Panel Data on the Changing Nature of Corporate Hierarchies - Rajan, Raghuram G; Wulf, Julie (The Review of Economics and Statistics, 2006)
Using a detailed database of managerial job descriptions, reporting relationships, and compensation structures in over 300 large U.S. firms, we find that firm hierarchies are becoming flatter. The number of positions reporting directly to the CEO has gone up significantly over time while the number of levels between the division heads and the CEO has decreased. More of these managers now report directly to the CEO and more are being appointed officers of the firm, reflecting a delegation of authority. Moreover, division managers who move closer to the CEO receive higher pay and greater long-term incentives, suggesting that all this is not simply a change in organizational charts with no real consequences. Importantly, flattening cannot be characterized simply as centralization or decentralization. We discuss several possible explanations that may account for some of these changes. Copyright by the President and Fellows of Harvard College and the Massachusetts Institute of Technology.